Activation of Hageman Factor (Factor XII) by Long-Chain Saturated Fatty Acids - Didisheim, Paul; Mibashan, R Sougin (Thrombosis and Haemostasis, 1963)
1. Long-chain saturated fatty acids accelerate the clotting of blood by activating Hageman factor (HF, factor XII). Their effect is proportional to their chain length.2. The hypothesis is discussed that long-chain saturated fatty acids in the circulating blood of man may exert a similar effect, and may thus be one of the factors in the etiology of clinical thrombosis.